2018
DOI: 10.1177/1558944718793972
|View full text |Cite
|
Sign up to set email alerts
|

Early Correction of Distal Radius Partial Articular Malunion Leads to Good Long-term Functional Recovery at Mean Follow-up of 4 Years

Abstract: Based on these findings, we recommend that early corrective osteotomies should be considered in young patients with intra-articular distal radius malunions before considering salvage procedures such as partial or complete wrist arthrodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…[ 7 ] Recently, corrective osteotomy for radius is an effective and classical treatment for DRF malunions. [ 8 , 10 ] Earlier, an opening wedge corrective osteotomy was widely used, which was via a dorsal approach followed by dorsal buttress plate fixation. [ 16 ] Open wedge osteotomy for radius could be performed with oscillating saw and osteotomes, and fixed with plate through a volar approach for Colles type fracture and a dorsal approach for Smith type fracture or a combined approach,[ 10 , 17 , 18 ] in which bone grafting for defect is required.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Recently, corrective osteotomy for radius is an effective and classical treatment for DRF malunions. [ 8 , 10 ] Earlier, an opening wedge corrective osteotomy was widely used, which was via a dorsal approach followed by dorsal buttress plate fixation. [ 16 ] Open wedge osteotomy for radius could be performed with oscillating saw and osteotomes, and fixed with plate through a volar approach for Colles type fracture and a dorsal approach for Smith type fracture or a combined approach,[ 10 , 17 , 18 ] in which bone grafting for defect is required.…”
Section: Discussionmentioning
confidence: 99%
“…The right time for surgery is as soon as possible as long as the bones are still in good condition and the wrist function is still adequate. In general, 5–8 weeks after fracture is a suitable time when it is still possible to make corrections easily and without a bone graft [6] . After 4–6 months from the onset of the fracture, correction becomes more difficult as callus remodeling has occurred [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study showed that total disability is decreased and patients return to work earlier than those corrected at later stages [2]. After 4 to 6 months of healing, the callus is remodeled and correction becomes much more difficult and increases morbidity for the patient [3].…”
Section: Timing Of Osteotomymentioning
confidence: 99%
“…For symptomatic patients for whom osteotomy is indicated, the timing of intervention is controversial, but there is some evidence that intervention as early as 6 weeks may be beneficial [2,3]. Regardless of timing, the goal is to restore both radiocarpal and distal radioulnar joint (DRUJ) congruence to improve pain and function and prevent future arthritis [4].…”
Section: Introductionmentioning
confidence: 99%